NARRATIVE RESEARCH TENTANG PENYESUAIAN AKADEMIK MAHASISWA TIDAK SEBIDANG PSIKOLOGI PENDIDIKAN SPS UPI 2019-2020 - Astari Mirisya, - (2022)
This research is a qualitative research that aims to explore, find out and re-explain in narrative form about self-adjustment experiences of Educational Psychology Department's non-linear students of SPS UPI in 2019-2020 when studying new and different knowledge. This study took students of Educational Psychology class 2019-2020 with a major background that was not from the Educational, Counseling and Psychology Department when they were undergraduates. The results of the study indicate that non-linear students: 1) felt the otherness or difference when adjusting to the environment and when participating in the learning process in the environment where they studied; 2) felt inferior before and during the adjustment process when they were studying new and different knowledge, and it accompanied by the efforts they make to reduce these feelings; and 3) had Self-compassion when they were realizing that the experiences and difficulties they experienced were also experienced by other non-linear when participating in the learning process.